2021
DOI: 10.1002/adfm.202102458
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide Filter and Dendrite Inhibitor: Highly Graphitized Wood Framework Inhibits Polysulfide Shuttle and Lithium Dendrites in Li–S Batteries

Abstract: The design and manufacture of advanced materials based on biomaterials provide new opportunities to solve many technological challenges. In this work, a highly graphitized wood framework (GWF) with a porous tunnel structure and microvilli is constructed as a multifunctional interlayer to improve the electrochemical performance of lithium–sulfur (Li–S) batteries. The GWF not only retains the 3D transport network of wood, but also offers increased deposition sites for polysulfides through the microvilli which gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 77 publications
(78 reference statements)
0
29
0
Order By: Relevance
“…For example, we reported previously a 3D conductive carbon framework with graphitic microvilli in the tunnel by using pine wood, and found that abundant microvilli were beneficial to the immobilization of polysulfides because they could offer more active sites and enhance the reaction kinetic of Li–S battery. [ 31 ] To expand the scope of the application of our research results, another kind of 3D conductive carbon framework is filled with carbon nanotubes to further use the microchannel space. On the other hand, perovskite compounds with oxygen vacancies are used as catalysts in microchannels to accelerate the conversion of polysulfides.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we reported previously a 3D conductive carbon framework with graphitic microvilli in the tunnel by using pine wood, and found that abundant microvilli were beneficial to the immobilization of polysulfides because they could offer more active sites and enhance the reaction kinetic of Li–S battery. [ 31 ] To expand the scope of the application of our research results, another kind of 3D conductive carbon framework is filled with carbon nanotubes to further use the microchannel space. On the other hand, perovskite compounds with oxygen vacancies are used as catalysts in microchannels to accelerate the conversion of polysulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectra (Figure 2b) display two peaks of D band (1346 cm −1 ) and G band (1578 cm −1 ) to reveal the amorphous structure and sp 2 ‐hybridized graphitic, respectively. [ 34 ] The intensity ratios of I D to I G are 0.99, 0.985, 0.98, 0.972 of the N/O‐HC700, N/O‐HC800, N/O‐HC900, N/O‐HC1000, respectively. These tiny changes can be assigned to the carbonization process in which graphitic carbon is easily formed at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Plating lithium in porous current collectors, which mitigates the volume change of anode, physically suppresses dendrites growth, and provides more electrical contact between lithium and conductor than 2D current collectors, is popularly researched to enhance the performances of lithium anodes. [266][267][268] Compared to 2D plane copper current collector, 3D porous carbon materials are lighter and more chemically stable. 269 In addition, the high surface area of porous structures is advantageous in terms of lowering the local current density and thus prolonging Sand's time.…”
Section: Hcps For Stabilizing a Li-metal Anodementioning
confidence: 99%